Analisis Berlangganan Iklan di Marketplace Facebook Dalam Meningkatkan Penjualan : Suatu Tinjauan Marketing Syariah pada Usaha Skincare Reglow - Mohamad Anang Prasetyo; Abdur Rahman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to find out how subscribing to advertisements on the Facebook marketplace affects the sales rate of the reglow skincare business and how the reglow skincare business marketing strategy is reviewed in sharia marketing. This study used a qualitative descriptive method, which is a method that is more adaptive when reality changes, directly represents the relationship between the researcher and the object of research, and is more perceptive and able to adapt to the impacts of the values patterns encountered. The analysis technique used was descriptive, namely data collection in the form of description and documentation through interviews and observation. The research results obtained showed that: (1) reglow skincare business markets its products through Instagram, Facebook, subscribing to Facebook ads, Shopee, and offline. (2) among the media used in marketing the products, subscribing to advertisements on Facebook is the most dominant. From June to October, the sales rate reached 1,947 compared to the others. (3) in the review of sharia marketing, the reglow skincare business is appropriate because there is a product guarantee, taking into account the aspect of its usefulness, the marketing is by the targets and the products are guaranteed to be halal, and have already had BPOM certificate.